Analysis of Internal Control of Good Corporate Governance and Fraud Prevention (Study at the Regional Government of Jambi City) - Netty Herawaty; Riski Hernando (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2020)
This study aims to analyze whether there is an influence of internal control on fraud prevention and Good Corporate Governance, and to analyze whether there is an effect of Good Corporate Governance on fraud prevention, and to analyze internal control against fraud prevention with Good Corporate Governance as intervening variable (Study at the Regional Government of Jambi City). This research method uses primary data by distributing questionnaires to all SKPDs of the Jambi government with 49 respondents using purposive sampling and returning 47 questionnaires. Methods of data analysis using SEM-PLS analysis (Structural Equation Modeling-Partial Least Square). The results of the study show that internal control does not affect fraud prevention, internal control does not affect Good Corporate Governance and Good Corporate Governance does not affect fraud prevention.